Polysomnography performed in the unattended home versus the attended laboratory setting--Sleep Heart Health Study methodology. - Iber, Conrad; Redline, Susan; Kaplan Gilpin, Adele M; Quan, Stuart F; Zhang, Lin; Gottlieb, Daniel J; Rapoport, David; Resnick, Helaine E; Sanders, Mark; Smith, Philip (Sleep, 2004)
STUDY OBJECTIVE: To compare polysomnographic recordings obtained in the home and laboratory setting. DESIGN AND SETTING: Multicenter study comparing unsupervised polysomnography performed in the participant's home with polysomnography supervised at an academic sleep disorders center, using a randomized sequence of study setting. Sleep Heart Health Study (SHHS) standardized polysomnographic recording and scoring techniques were used for both settings. PARTICIPANTS: 64 of 76 non-SHHS participants recruited from 7 SHHS field sites who had both a laboratory and home polysomnogram meeting acceptable quality criteria. MEASUREMENTS AND RESULTS: Median sleep duration was greater in the home than in the laboratory (375 vs 318 minutes, respectively, P < .0001) as was sleep efficiency (86% vs 82%, respectively, P < .0024). Very small, but significant increases in percentage of rapid eye movement sleep and decreases in stage 1 sleep were noted in the laboratory. Employing multiple definitions of respiratory disturbance index (RDI), median RDI was similar in both settings (for example, RDI with 3% desaturation: home 12.4, range 0.6-67; laboratory 9.5, range 0.1-93.4, P = .41). Quartile analysis of laboratory RDI showed moderate agreement with home RDI measurements. Based on the mean of laboratory and home RDI and using a cutpoint of 20, there was a biphasic distribution, with the RDI 3% above 20 being more common in the recordings performed in the laboratory than in the home and below 20 being more common in the recordings performed in the home than in the laboratory. These differences could not be attributed to quality of recording, age, sex, or body mass index. CONCLUSIONS: Using SHHS methodology, median RDI was similar in the unattended home and attended laboratory setting with differences of small magnitude in some sleep parameters. Differences in RDI between settings resulted in a rate of disease misclassification that is similar to repeated studies in the same setting.
Keywords: Adult; Aged; Body Mass Index; Clinical Laboratory Techniques; Cohort Studies; Health Status; Home Care Services; Humans; Middle Aged; Polysomnography; Sleep Apnea Syndromes; Sleep, REM

Polysomnographic predictors of blood pressure and hypertension: is one index best? - Redline, Susan; Min, Nancy I; Shahar, Eyal; Rapoport, David; O'Connor, George (Sleep, 2005)
STUDY OBJECTIVES: Numerous indexes derived from polysomnography are available to characterize sleep-disordered breathing, with no consensus over which measures best predict clinical outcomes. This study addresses the relative merits of using alternative polysomnography indexes by characterizing the consistency and strength of the association of each index with blood pressure and hypertension. DESIGN: Cross-sectional analyses of the association of alternative polysomnography indexes with blood pressure and hypertension were performed in construction and validation data sets. Linear and logistic regression models were used to identify the best variable sets. PATIENTS: Data were obtained from 6433 men and women (age 62.9 +/- 11.0 years, 52.8% women) who participated in the Sleep Heart Health Study. RESULTS: In multivariable models, most indexes showed weak linear associations with systolic, with slightly stronger associations for diastolic blood pressure, and the log odds of hypertension. No single index showed consistent superiority over others. Systolic blood pressure, diastolic blood pressure, and hypertension each were associated with distinct sets of polysomnography variables. Slightly more-consistent associations were demonstrated for indexes that included hypopneas that were linked with either a 3% or 4% desaturation level than indexes that did not require hypopneas to have linked desaturation. For indexes that combined apneas and hypopneas, there was no evidence that linking obstructive apneas to desaturation or arousal altered prediction compared with counting all apneas. CONCLUSION: In summary, using a rigorous cross-validation assessment, we did not identify a clear superiority of any single index for blood pressure or hypertension prediction. Detailed analyses of alternative definitions of the respiratory disturbance index support current scoring guidelines, where desaturation criteria are recommended for hypopneas but not apneas.
Keywords: Blood Pressure; Cross-Sectional Studies; Female; Humans; Hypertension; Male; Middle Aged; Polysomnography; Predictive Value of Tests; Reproducibility of Results; Severity of Illness Index; Sleep Apnea, Obstructive

Sleepiness, quality of life, and sleep maintenance in REM versus non-REM sleep-disordered breathing. - Chami, Hassan A; Baldwin, Carol M; Silverman, Angela; Zhang, Ying; Rapoport, David; Punjabi, Naresh M; Gottlieb, Daniel J (Am J Respir Crit Care Med, 2010)
RATIONALE: The impact of REM-predominant sleep-disordered breathing (SDB) on sleepiness, quality of life (QOL), and sleep maintenance is uncertain. OBJECTIVE: To evaluate the association of SDB during REM sleep with daytime sleepiness, health-related QOL, and difficulty maintaining sleep, in comparison to their association with SDB during non-REM sleep in a community-based cohort. METHODS: Cross-sectional analysis of 5,649 Sleep Heart Health Study participants (mean age 62.5 [SD = 10.9], 52.6% women, 22.6% ethnic minorities). SDB during REM and non-REM sleep was quantified using polysomnographically derived apnea-hypopnea index in REM (AHI(REM)) and non-REM (AHI(NREM)) sleep. Sleepiness, sleep maintenance, and QOL were respectively quantified using the Epworth Sleepiness Scale (ESS), the Sleep Heart Health Study Sleep Habit Questionnaire, and the physical and mental composites scales of the Medical Outcomes Study Short Form (SF)-36. MEASUREMENTS AND MAIN RESULTS: AHI(REM) was not associated with the ESS scores or the physical and mental components scales scores of the SF-36 after adjusting for demographics, body mass index, and AHI(NREM) x AHI(REM) was not associated with frequent difficulty maintaining sleep or early awakening from sleep. AHI(NREM) was associated with the ESS score (beta = 0.25; 95% confidence interval [CI], 0.16 to 0.34) and the physical (beta = -0.12; 95% CI, -0.42 to -0.01) and mental (beta = -0.20; 95% CI, -0.20 to -0.01) components scores of the SF-36 adjusting for demographics, body mass index, and AHI(REM). CONCLUSIONS: In a community-based sample of middle-aged and older adults, REM-predominant SDB is not independently associated with daytime sleepiness, impaired health-related QOL, or self-reported sleep disruption.
Keywords: Aged; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Quality of Life; Sleep; Sleep Apnea Syndromes; Sleep, REM